Safety aspect of Kelang Port Management (KPM) Sdn. Bhd. with a particular reference to stevedoring operation of cargo services department / Norainy Othman - Othman, Norainy (2007)
Cargo Services Department is the largest of the seven departments in the fold of Kelang Port Management (KPM) Sdn. Bhd. It employs 2,300 employees of the total 4,000 under the KPM payroll the total compliment; 1,500 belongs to the industrial manual group namely the stevedores. The port has only recently been privatised and due to the country's rapid economic development, more ships are berthing in bigger volume of cargoes. As a result of this, there are bigger loads to be handled and has to be done fast. This has resulted in an increase in the number of accidents and has dented the management's coffer in term of medical bills, insurance premium and man hour loss. In order to reduce the high accident rate during stevedoring operations, KPM has taken certain measures including establishing Loss Reporting System, Emphasizes on the role of Fire Services Department, the formation of Dangerous Good Section and the formation of Risk Management Department. The research conducted found that there are two main causes of high accident rate during stevedoring operations and another related cause. Stevedores unsafe act and lack of enforcement are the main causes of accident happened and lack of housekeeping work is the other related factor. Finally, recommendations forwarded are based on the causes of accident identified. The recommendations include training of stevedores, regular briefing to the stevedores before commencing work, safety inspection and lastly a proper housekeeping.